Electrical analysis and ultra-fast sequential imaging of surface barrier discharge with streamer-leader sequence generated with 100 kHz frequency at the water interface. (10th September 2019) - Synek, P; Akishev, Y; Petryakov, A; Trushkin, N; Voráč, J; Hoder, T
Abstract: A time resolved study of the electrical parameters and ultra-fast 2D imaging of the surface barrier discharge emerging from liquid electrodes in atmospheric pressure argon is reported. Analysing the electrical measurements and the charge-voltage (Q-V) plots, a resistive component of the electrical system impedance is revealed and described by the logical progression of the method to current-voltage (I–V) plots. The necessity to include a resistive component in the simplest equivalent circuit is demonstrated. Net discharge current, charge or effective gap voltage are linked to the light emission. A special nanosecond-gated camera enabling multiple expositions within a few hundreds of nanoseconds is applied and reveals the spatiotemporal development of the discharge luminosity. Propagation of the streamer-leader stepping sequence on the dielectric surface is observed and the mean velocities and axial light-emission development is quantified. A light emission of an excited gas prior to and after the discharge's main current peak is detected revealing an increased activity between the subsequent discharges. This is caused by the high pre-ionisation of the gas volume and the intensive charging of the surface. The generation of subsequent streamers emerging from/between the surface charge domains is evidenced.